A Black Thang: Black Nia F.O.R.C.E, Radical Student Reading Circles, and Intellectual Freedom. (20th September 2022) - Myers, Joshua
Abstract : One of the central themes of Black student activism in the latter half of the twentieth century was re-education. Finding the curriculums confronted in their schooling to be inadequate, student activists fought for Black Studies. But they also built alternatives to formal schooling. These reading circles and study groups became incubators for radical thinking, places that were free from the authority of campus administrations. This essay explores the prominence of reading circles in the context of Black student struggles at Howard University in the 1980s, through a focus on the organization, Black Nia F.O.R.C.E. It seeks to demonstrate that the preface for radical action, for their radical orientation, was knowledge and that ultimately, it was within self-determined intellectual spaces, where we find the true roots of "Black Study."